Radio and HIV/AIDS : making a difference : a guide for radio practitioners, health workers and donors - Adam, Gordon (UNAIDS GenevaCH, 1999)
Contains practical guidelines for planning, researching, designing, producing and evaluating HIV/AIDS programmes on the radio. Focuses on the practical issues and approaches involved but does not attempt to cover the technicalities of radio production.